Advance and Prospect of Nanoscale Chinese Medicine - Rina Wu (Nano Biomedicine and Engineering, 2010)
Over the past few years, nanoscale Chinese medicine has emerged as a new exciting field in which theoretical and experimental studies of structure and function of nanoscale Chinese drugs have become a focus, and the importance of quality standardization of nanoscale medicament of Chinese traditional medicine as specific drugs to the fundamental development in traditional Chinese drugs has begun to be recognized. In particular, Chinese medicine dispersion, surface potentials, envelopment ratio, loading drug amounts, in vivo metabolism dynamics, bio-distribution, drug-releasing in vitro, etc., have become a new interdisciplinary frontier in life science and Chinese traditional medicine. There is an increasing need for a more systematic study of the basic issues involved in traditional Chinese medicine and a more active participation of researchers in the application area of nanoscale traditional Chinese drugs. Some advances have been and are being made in nanoscale Chinese herbs, mineral medicine including mongolia drugs such as cinnabar, with enormous prospect in clinical disease therapy. Here we review some of the main advances in this field over the past few years, explore the application prospects, and discuss the concepts, issues, approaches, and challenges, with the aim of stimulating a broader interest in developing nanoscale Chinese medicine.